2005
DOI: 10.1152/jn.00721.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Subcortical Correlates of Electroencephalographic Alpha Rhythm Modulation

Abstract: Neural correlates of electroencephalographic (EEG) alpha rhythm are poorly understood. Here, we related EEG alpha rhythm in awake humans to blood-oxygen-level-dependent (BOLD) signal change determined by functional magnetic resonance imaging (fMRI). Topographical EEG was recorded simultaneously with fMRI during an open versus closed eyes and an auditory stimulation versus silence condition. EEG was separated into spatial components of maximal temporal independence using independent component analysis. Alpha co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
268
3
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(313 citation statements)
references
References 50 publications
37
268
3
5
Order By: Relevance
“…Low frequency sensorimotor rhythms have been associated with reciprocal thalamic and basal ganglia projections to cortex [Brown, 2003;Feige et al, 2005;Pfurtscheller and Lopes da Silva, 1999;Schnitzler et al, 2006]. Assuming that these low frequency rhythms reflect inhibition of a cortical region [Mazaheri et al, 2009], the decrease in power that we measure in a and b1 may reflect a disinhibition or preparation of cortical structures.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Low frequency sensorimotor rhythms have been associated with reciprocal thalamic and basal ganglia projections to cortex [Brown, 2003;Feige et al, 2005;Pfurtscheller and Lopes da Silva, 1999;Schnitzler et al, 2006]. Assuming that these low frequency rhythms reflect inhibition of a cortical region [Mazaheri et al, 2009], the decrease in power that we measure in a and b1 may reflect a disinhibition or preparation of cortical structures.…”
Section: Discussionmentioning
confidence: 80%
“…Power decreases in low frequency sensorimotor rhythms are distributed over larger areas of cortex [Crone et al, 1998b;Miller et al, 2007]. These spectral changes are associated with different processes: broadband power change is associated with local neuronal processing [Manning et al, 2009;Miller et al, 2009a], whereas low frequency oscillations reflect an aspect of subcortical-cortical interaction [Brown, 2003;Feige et al, 2005;Pfurtscheller and Lopes da Silva, 1999;Schnitzler et al, 2006]. Functional MRI BOLD change has also been compared with electrocortial stimulation mapping, and has been shown to be adequately sensitive but less specific in predicting electrocortical stimulation sites [Pouratian et al, 2002;Rutten et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, simultaneous EEG/ fMRI has been successfully applied to investigate cognitive phenomena such as performance monitoring (Debener et al, 2005) and sustained attention (Eichele et al, 2005). Apart from epilepsy research most studies have focused on the BOLD correlates of ongoing oscillatory activity during resting state (i.e., recorded while the subject was quietly lying in the scanner, with no explicit task), focusing on the posterior alpha rhythm and, to a lesser extent, the beta rhythm (Feige et al, 2005;Goldman et al, 2002;Goncalves et al, 2006;Laufs et al, 2006Laufs et al, , 2003aMoosmann et al, 2003). In these studies, the general idea has been that spontaneous fluctuations in the amplitude of a given oscillatory signal can be correlated with spontaneous fluctuations in the BOLD signal.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the BOLD correlates of spontaneous fluctuations in alpha activity (Feige et al, 2005;Goldman et al, 2002;Goncalves et al, 2006;Laufs et al, 2006Laufs et al, , 2003aMoosmann et al, 2003) have shown that the expected posterior visual regions and also other regions across the cortex are negatively correlated with posterior alpha fluctuations. Recent findings suggest that there is considerable individual variation in areas that correlate with the alpha fluctuations and that these can be linked to differences in the total power spectrum of an individual (Goncalves et al, 2006;Laufs et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…EEGfMRI recording has been used for localizing epileptic spikes (Warach et al, 1996;Seeck et al, 1998;Krakow et al, 1999;Goldman et al, 2000;Baudewig et al, 2001;Lemieux et al, 2001;Salek-Haddadi et al, 2002;Sommer et al, 2003), determining sources of event related potentials (Bonmassar et al, 1999;Kruggel et al, 2000;Liebenthal et al, 2003;Sommer et al, 2003), or correlating brain rhythms with hemodynamic activities (Goldman et al 2002, Laufs et al 2003, Moosmann et al 2003, Feige et al 2005, de Munck et al 2007). …”
Section: Introductionmentioning
confidence: 99%